Pengenalan Konversi Energi Terbarukan sebagai Penguatan Kualitas Pembelajaran Rekayasa dan Teknologi di MTs Sains Karimiyya Kebasen Kabupaten Banyumas - Sehah, Muhammad; Hartono, Hartono; Abdulatif, Raden Farzand; Sugito, Sugito (Jurnal Serambi Abdimas, 2025)
Education in Indonesia continues to face significant challenges in achieving equitable access and improving quality, thereby requiring the strengthening of teacher competencies, the development of a relevant curriculum, and the provision of adequate learning facilities. Through the implementation of the Independent Learning (Merdeka Belajar) Curriculum and the Pancasila Student Profile Strengthening Project (Proyek Penguatan Profil Pelajar Pancasila, P5), the government aims to promote a more flexible, contextual, and character-oriented learning approach that fosters 21st-century skills. At MTs Sains Karimiyya Kebasen, Banyumas Regency, the implementation of the engineering and technology theme within the P5 program aligns with the school’s vision as a science-based Islamic institution. The research-based community service activity focusing on renewable energy conversion serves as a practical step toward realizing this vision, while also fostering creativity, innovation, and environmental awareness among students. The renewable energy conversion outreach activity at MTs Sains Karimiyya Kebasen proved effective in enhancing students’ understanding of energy conversion principles through the application of solar power kits and simple electrical generators as learning aids. A comparison of pre-test and post-test results demonstrated a significant improvement across all assessed aspects, indicating that practice- and demonstration-based learning effectively increased student engagement, enthusiasm, and conceptual understanding. Evaluation results based on questionnaires further revealed highly positive responses toward the use of renewable energy conversion learning aids. The strong enthusiasm among participants also suggests that the use of such teaching tools effectively stimulates students’ curiosity and interest, making teaching-aid-based learning methods highly feasible for further development to improve the quality of science education.